The Job Satisfaction of Non-Civil Servant Nurses in Indonesia Public Hospitals - Tri Siwi Agustina; Yuli Ismiati; Sutinah Sutinah (Universitas Muhammadiyah Yogyakarta, 2020)
Nurse’s job satisfaction ia an important factor that must be strived by the management of hospital because the impact of job satisfaction is not only on the nurse itself bu also have an impact on the patient and hospital’s image also. This is a descriptive quantitative research with cross sectional approach. This study was conducted involving 74 non-civil nurses who worked in surgery inpatient care of “X” public hospital in East Java, Indonesia. The result show that career development affect nurses’s job satisfaction through organizational commitment as mediating variables. Compensation affect nurses’s job satisfaction through organizational commitment as mediating variables